Read about communism but dont take up arms, says ex cop - Bernama, . (FMT Media Sdn Bhd., 2022)
KUALA LUMPUR: Continuous monitoring by the Special Branch on the activities and actions of followers of communism will be able to curb its re-emergence in the country.